PENGARUH SOCIAL MEDIA MARKETING TERHADAP LOYALITAS MEREK (Studi Pada Akun Instagram @teraskomika Malang) - NEVIANI, CHAERISA ZELINDA (Jurnal Ilmiah Mahasiswa FEB, 2018)
The aim of this study is to examine the affect of social media marketing on brand loyalty. The independent variables tested in this research are advantageous campaign, relevant content, frequent updates its content, popular content and various platform and application which tested its influence on brand loyalty on account instagram @teraskomika in Malang city. In this study, the scope of the study consists of customer who make a visit for a purchase of products in the cafe Teras Komika and follow @teraskomika. The number of respondents in this study was determined as 126 respondents selected using purposive sampling method. The collected data were analyzed using multiple linear regression. The result showed that the variable Relevant Conten and Popular Content has significant effect on brand loyalty, while variable Advantageous Campaign, Frequently Updates its Contents and Various Platform and Application has no significant effect on brand loyalty.Keywords: brand loyalty, advantageous campaign, relevant content, frequently updates its content, popular content, various platform and application